Effective factors on brace compliance in idiopathic scoliosis: a literature review. (16th November 2020) - Rahimi, Sara; Kiaghadi, Adele; Fallahian, Nader
Abstract: Objectives: Compliance plays a major role in the success of brace treatment and is influenced by factors such as the kind of brace, measurements method, regimen for brace wear, pattern wearing at night/day or full/part time and another factor is also psychological condition of the wearer. The objective of this review is to assess affecting factors on compliance of spinal braces in idiopathic scoliosis. Materials and methods: The guideline of the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) was used for conducting review and assessing the quality of evidence. The search in Pubmed databases had 175 results of which 17 articles met the inclusion criteria. Effective factors on compliance were extracted and categorized into six groups based on type of brace, measurement method, age, day/night time pattern wearing, full/part time wearing and psychological aspect that can improve the result of spinal brace treatment in idiopathic scoliosis. Results: The results demonstrated that the type of braces determines structure and appearance and affects compliance. Psychological aspects, age, brace wear pattern (daytime or nighttime or part-time versus fulltime) and the assessment method (using temperature versus pressure sensors) can affect recorded compliance. Conclusions: Compliance can be augmented by considering factors in the design and delivery of the brace. Superior appearance and comfortable within the brace can improve psychological acceptance and improve the compliance. Lower age, involving the patient in treatment procedure, considering the child habits, and improved family awareness of the treatment plan of idiopathic scoliosis can also improve overall compliance of the brace. Implications for rehabilitation: This article reviews factors that affect compliance with orthotic treatment in idiopathic scoiliosis.